The practice of human rights: tracking law between the global and the local - Goodale, Mark; Merry, Sally Engle (Cambridge studies in law and society, 2007)
Human rights are now the dominant approach to social justice globally. But how do human rights work? What do they do? Drawing on anthropological studies of human rights work from around the world, this book examines human rights in practice. It shows how groups and organizations mobilize human rights language in a variety of local settings, often differently from those imagined by human rights law itself. The case studies reveal the contradictions and ambiguities of human rights approaches to various forms of violence. They show that this openness is not a failure of universal human rights as a coherent legal or ethical framework but an essential element in the development of living and organic ideas of human rights in context. Studying human rights in practice means examining the channels of communication and institutional structures that mediate between global ideas and local situations. Suitable for use on inter-disciplinary courses globally